Optimizing the Quality Improvement of Students through the Qur'an Translation Training Program - Faisal, Faisal; Abdullah, Abdullah; Mudarris, Badrul (Journal of Educational Management Research, 2024)
The study was conducted to determine the contribution of PPTQ in improving the quality of students, especially improving the quality of Islamic boarding schools in understanding the contents of the Qur'an. The study was conducted at the Nurul Jadid Islamic Boarding School using a qualitative research method of the case study type. The results of the study indicate that the planning process at PPTQ is carried out through deliberations involving all administrators, reflecting traditional values and strong collaboration. Program control is carried out by the Supervisor, who forms a clear and effective organizational structure to oversee the implementation of activities. A tiered learning system is applied to facilitate structured and progressive learning, while teamwork between administrators ensures that all activities run according to plan. Quality improvement is achieved through ongoing feedback from alumni and students, as well as through routine evaluations carried out by the supervisor and administrators. The results of the study are expected to be a tool for administrators to maintain consistency in improving the quality of students and Islamic boarding schools.